THE EFFECTIVENESS OF THE CIRCUIT LEARNING MODEL IN IMPROVING STUDENT LEARNING OUTCOMES IN THE SUBJECT OF ALQUR'AN HADIST AT MTs ALWASHLIYAH PASAR MIRING - Fadhilah, Rizka; Lubis, Khairuddin; Harahap, Hotni Sari (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2023)
This study aims to find out how a teacher's efforts in increasing student learning activeness in Qur'an hadith lessons through the circuit learning method. In this writing also provides a way of how to use the circuit learning method in learning the Qur'an hadith. Using this method is expected to affect student activity in the learning process and end in an increased understanding of the Qur'an and Hadith lessons. The circuit learning learning model is one of the strategies used in implementing the learning process through a group approach by requiring students to develop words in their own language related to the material that has been studied in groups. This research took place at MTs Alwashliyah. The results of this study note that the circuit learning method is effective in increasing student learning activity as seen from the participation of students in answering and providing comments in learning using the students' own language.